Theology as improvisation : a study in the musical nature of theological thinking - Crawford, Nathan. (Studies in Systematic Theology, 2013)
In Theology as Improvisation , Nathan Crawford reimagines the possibilities for how theology thinks God within a postmodern world. He argues that theology is improvisation by analyzing the nature of attunement within theological thinking and how this opens certain possibilities for theology. He does so by engaging a number of thinkers, including Martin Heidegger, Jacques Derrida, David Tracy, and Saint Augustine. He navigates the nature of thinking God in a postmodern world by using these thinkers to offer critiques of onto-theological thinking and totalizing systems while also following their embrace of the fragment and focus upon the nature of thinking as attunement. The result is a unique way of approaching theological thinking in our contemporary context.